SURGICAL SITE INFECTIONS BY METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS AMONG POST OPERATIVE PATIENTS - ONZERE, BARSANTER; MUTHARIA , PATRICK (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
The aim of this study was to determine surgical site infections by Methicillin Resistant Staphylococcus aureus among post operative patients in MeTRH. The main objective was to identify Methicillin resistant Staphylococcus aureus, isolated from wound swabs of surgical patients at Meru Teaching and Referral Hospital (MeTRH). The study utilized standard microbiological procedures such as culturing in blood agar, biochemical test such as catalase and coagulase tests for confirmation of Staphylococcus aureus and microbial susceptibility profile on Mueller Hinton agar using cefoxitin and or oxacillin drugs to identify Methicillin resistant Staphylococcus aureus. Statistical analysis revealed a significant increase in the incidence of MRSA in surgical sites of post-operative patients. This can be attributed to certain health care as well as patient factors that play a role towards this increase. Proper infection prevention and control measures need to be put in place in order to reduce risk of outbreaks of MRSA.